Silencing amorpha-4,11-diene synthase Genes in Artemisia annua Leads to FPP Accumulation - Catania, Theresa M.; Branigan, Caroline A.; Stawniak, Natalia; Hodson, Jennifer; Harvey, David; Larson, Tony R.; Czechowski, Tomasz; Graham, Ian A. (Frontiers in Plant Science, 2018)
Artemisia annua is established as an efficient crop for the production of the anti-malarial compound artemisinin, a sesquiterpene lactone synthesised and stored in Glandular Secretory Trichomes (GSTs) located on the leaves and inflorescences. Amorpha-4,11-diene synthase (AMS) catalyses the conversion of farnesyl pyrophosphate (FPP) to amorpha-4,11-diene and diphosphate, which is the first committed step in the synthesis of artemisinin. FPP is the precursor for sesquiterpene and sterol biosynthesis in the plant. This work aimed to investigate the effect of blocking the synthesis of artemisinin in the GSTs of a high artemisinin yielding line, Artemis, by down regulating AMS. We determined that there are up to 12 AMS gene copies in Artemis, all expressed in GSTs. We used sequence homology to design an RNAi construct under the control of a GST specific promoter that was predicted to be effective against all 12 of these genes. Stable transformation of Artemis with this construct resulted in over 95% reduction in the content of artemisinin and related products, and a significant increase in the FPP pool. The Artemis AMS silenced lines showed no morphological alterations, and metabolomic and gene expression analysis did not detect any changes in the levels of other major sesquiterpene compounds or sesquiterpene synthase genes in leaf material. FPP also acts as a precursor for squalene and sterol biosynthesis but levels of these compounds were also not altered in the AMS silenced lines. Four unknown oxygenated sesquiterpenes were produced in these lines, but at extremely low levels compared to Artemis non-transformed controls. This study finds that engineering A. annua GSTs in an Artemis background results in endogenous terpenes related to artemisinin being depleted with the precursor FPP actually accumulating rather than being utilised by other endogenous enzymes. The challenge now is to establish if this precursor pool can act as substrate for production of alternative sesquiterpenes in A. annua.